Penerapan ekonomi sirkular: Tantangan dan peluang bagi bisnis dalam mewujudkan pembangunan berkelanjutan - Nafi, Agnizuhria Imtinan (Maliki Interdisciplinary Journal, 2024)
A new paradigm in the pursuit of sustainable development is the circular economy. The 3Rs (reduce, reuse, recycle) and waste minimization are used to highlight the concept's emphasis on resource efficiency. Businesses may increase operational effectiveness, cut expenses, and add value by implementing the circular economy into their operations and offering eco-friendly goods and services. But there are drawbacks to moving toward a circular economy model as well, such shifting consumer behavior, reorganizing the supply chain, and investing in new technology. In addition to identifying the variables that encourage and impede the transition process, this study intends to investigate the possibilities and obstacles that businesses have while implementing circular economy practices. The results of this study should give interested parties important information on how to apply the circular economy to achieve sustainable development.